MICROPHONE FRONT CAVITY DEPTH MEASUREMENT USING NON-CONTACT METHOD AT NATIONAL MEASUREMENT STANDARDS – NATIONAL STANDARDIZATION AGENCY OF INDONESIA - Chery Chaen Putri; Denny Hermawanto (Badan Standardisasi Nasional, 2019)
Front cavity depth of microphone has influence in the determination of laboratory standard microphone sensitivity. Therefore this parameter is included in the measurement uncertainty budget. To determine microphone sensitivity accurately, it is necessary to measure the actual front cavity depth instead of using nominal value. This paper explains the measurement of LS1P and LS2P standard microphone front cavity depth using optical depth measurement facilities at SNSU-BSN and its effect on determining microphone sensitivity. The measurement was obtained from 4 positions distributed over the diaphragm for each microphone. The front cavity depth measurement result for LS1P is 1,94 mm ± 0,01 mm and for LS2P is 0,48 mm ± 0,01 mm These results comply with IEC 61094 Measurement Microphones-Part 2: Primary Method for Pressure Calibration of Laboratory Standard Microphones by Reciprocity Technique as the results are within the permissible range.